A method of marking the limbus during X-ray localization of IOFB in the presence of apparent chemosis or scleral subconjunctival hemorrhage - N.V. Malachkova; I.A. Gabruk; I.I. Gabruk; O.O. Andrushkova (Ukrainian Society of Ophthalmologists, 2020)
The method proposed for marking the limbus during X-ray localization of IOFB in the presence of apparent chemosis or scleral subconjunctival hemorrhage is based on the use of a ring-shaped limbus marker made from 0.5-0.7-mm stainless steel wire. Rings with external diameters of 10, 11 and 12 mm are used for examining eyes of different sizes. A ring of the appropriate size is placed on the cornea against the limbus to perform X-ray examination. It is well fit in the specified position due to hypertrophy of the conjunctiva surrounding the cornea, and corresponds to the conjunctival attachment to the limbus. Orbit X-ray is performed, quality of X-ray films is assessed and IOFB position in the eye is calculated using the technique of Comberg-Baltin or Abalikhin-Pivovarov. In 12 patients, IOFB was successfully removed based on the data obtained from the use of this method. The accuracy of IOFB X-ray localization by means of the ring-shaped limbus marker was found to be the same as that by means of the Baltin's prosthesis.